Antibiotic Susceptibility of Staphylococcus aureus Isolated from Chicken Eggs, Eastern Ethiopia - Kemal, Jelalu; Beji, Wakene; Tesfamariam, Gebregeorgis (East African Journal of Sciences, 2021)
Introduction: Staphylococcus aureus is responsible for a variety of infections in humans and animals that can pose a major public health burden in many countries, including Ethiopia. Objectives: This study was aimed to isolate Staphylococcus aureus present on the shell surfaces and in the contents of chicken eggs, and determine antibiotic susceptibility patterns. Material and Methods: One hundred seventy-four (174) egg samples were obtained from open market and 161 from poultry farm. The surfaces of eggs were sampled using a sterile cotton swab. After sterilizing the shells, the egg contents were sampled. Identification of Staphylococcus aureus was done based on culture characteristics, and biochemical tests. The isolates were subjected to antibiotic susceptibility testing using disc diffusion method. Results: A total of 93 (27.8%) Staphylococcus aureus samples were isolated. From these, 28 (17.4%) were from Haramaya University poultry farm while 65 (37.4%) were from market. In addition, 63 (18.8%) were from the shell while 30 (8.9%) were from the egg content. The occurrence of Staphylococcus aureus in the egg shell from open markets was significantly higher than the content from the egg shells obtained from farms (P = 0.021). The level of Staphylococcus aureus content was also significantly higher in the market (P = 0.003). All 76 Staphylococcus aureus isolates were resistant to at least one of the antimicrobials tested with the overall value 3.9–92.0% level of resistance pattern showing higher resistant to penicillin (92%) and ampicillin (89.5%). A lower level of resistance was observed to chloramphenicol, gentamycin and ciprofloxacin with complete susceptibility to vancomycin. Multiple drug resistance was detected in 86.8% of the Staphylococcus aureus isolates. Conclusion: The study showed a significant level of Staphylococcus aureus with considerable antibiotic resistant pattern. Further studies are needed to better define bacterial resistance to antibiotic agents with emphasis on surveillance of multiple drug resistance.